Effect of Post-Acute Kidney Injury Use of Renin-Angiotensin Inhibitors on Long-term Mortality and Major Adverse Kidney Events: A 5-year Retrospective Observational Cohort Study - Byorn W.L. Tan; Bryce W.Q. Tan; K. Akalya; Wei-Zhen Hong; Yi Da; Sanmay Low; Wan-Ying Ng; Horng-Ruey Chua (Kidney Medicine)
Rationale & Objective: Acute kidney injury (AKI) is common in hospitalized adults and a risk factor for chronic kidney disease and mortality. The effect of angiotensin-converting enzyme inhibitors (ACEi) or angiotensin receptor blockers (ARBs) post-AKI on mortality and long-term kidney function remains unclear. Study Design: Propensity-weighted retrospective observational cohort study. Setting & Participants: A total of 3,289 patients with AKI admitted to a tertiary care hospital from November 2015-October 2016, with follow-up until September 2020. Exposures: ACEi/ARB use within 180 days post-AKI. Outcomes: All-cause mortality, and major adverse kidney events (MAKE) as defined by composite of renal replacement therapy post-AKI, sustained estimated glomerular filtration rate (eGFR) decline >30% from baseline, or eGFR ≤15 mL/min/1.73 m2. Analytical Approach: We generated propensity weights for ACEi/ARB use post-AKI, using age, sex, comorbid conditions, prior medication, intensive care unit admission, severe sepsis, and index AKI Kidney Disease: Improving Global Outcomes severity. Cox proportional hazard models were used to test associations of post-AKI ACEi/ARB with mortality, MAKE, and joint models for eGFR slopes. Results: A total of 2,309 (70.2%) participants died or experienced MAKE by end of follow-up. 161 (4.9%) and 406 (12.3%) patients initiated or resumed prior ACEi/ARB use within 180 days post-AKI, respectively. Although the overall cohort had no significant mortality association with post-AKI ACEi/ARB use, a significant association with lower mortality was observed in patients with KDIGO 3 AKI (HR, 0.40; 95% CI, 0.21-0.75; Pinteraction = 0.003). However, post-AKI ACEi/ARB use was associated with increased MAKE in patients without cardiovascular indications for ACEi/ARB use (HR, 1.52; 95% CI, 1.17-1.98; Pinteraction = 0.03). Although post-AKI use of ACEi/ARB was associated with acute eGFR decline (initial eGFR change −2.3 mL/min/1.73 m2/year; 95% CI, −3.1 to −1.5; P < 0.001), no association with longer-term eGFR decline was observed. Limitations: Retrospective observational study on heterogeneous AKI cohort without data on ACEi/ARB cumulative exposure. Conclusions: Early ACEi/ARB post-AKI was not associated with better long-term survival or kidney function but was associated with lower mortality in patients with KDIGO 3 AKI. Plain Language Summary: Acute kidney injury (AKI) is common in hospitalized adults and increases the risk of death and kidney failure. Although angiotensin-converting enzyme inhibitors (ACEis) or angiotensin receptor blockers (ARBs) have been widely used in proteinuric kidney disease to slow kidney function decline, the effect of ACEi/ARB use post-AKI on long-term kidney function remains unclear. In this 5-year study of 3,289 patients with AKI, we found that although patients experienced a transient decrease in kidney function following early ACEi/ARB initiation after their kidney injury, long-term kidney function trajectory and survival in these patients were similar to patients without early ACEi/ARB use. However, ACEi/ARB use after an AKI may reduce the long-term risk of death in patients with severe AKI. Additionally, we noted sustained kidney function deterioration in a subgroup of patients on ACEi/ARB early post-AKI in the absence of cardiovascular indications. These observations suggest that clinicians should adopt more individualized approaches to early ACEi/ARB administration post-AKI.